Peran Badan Siber dan Sandi Negara (BSSN) dalam Arsitektur Keamanan Siber Indonesia - Hesti Rosdiana; Reja Reja; Bintang Hafizh Setiawan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This paper reviews the dynamics of cybersecurity in Indonesia, focusing on the role of the Indonesian National Cyber and Crypto Agency (BSSN) in Indonesia’s cybersecurity architecture. The conceptual framework used is cyber security to analyze cybersecurity phenomena in Indonesia and multi-level cybersecurity governance as a tool for analyzing the role of BSSN in the field of cybersecurity. A descriptive qualitative approach is the main methodological approach in this study. With this approach, this study attempts to describe the role of BSSN in Indonesia’s cybersecurity architecture. Data collection was carried out through a literature study obtained from BSSN’s main documents, official reports, and related journal articles. The findings show that BSSN has a strategic role in Indonesian cybersecurity. This strategic role is demonstrated by BSSN’s various achievement in cybersecurity, such as the drafting of a national cybersecurity bill, the development of human resources capacity in the cyber field and the establishment of cooperation with various parties, both domestically and internationally.